Institutional Gasifier Stove: A Sustainable Prospect for Institutional Cooking - Ale, Bhakta B.; Bhattarai, Nawaraj; Gautam, Jitendra; Chapagain, Pradeep; Pushpa, K. C. (Journal of the Institute of Engineering, 2009)
Gasifier stove can act as a simple and very important device for an energy sector which can improve cooking and kitchen environment. It would be more worthy if it is used for roadside hotels, hostels, schools, barracks, etc. where cooking is used for a large number of people. Taking this into consideration, a study had been conducted by studying the performance of the existing modified AIT model gasifier at NAST and then fabricating new institutional gasifier with further modification. The newly fabricated gasifier has better thermal efficiency compared to that of the modified gasifier present in NAST when tested with different types of fuel. The newly fabricated gasifier (IGS-2F) has an average efficiency of about 19% compared to modified gasifier (IGS-2M) which has an average efficiency of 17%. The pine cone has the highest efficiency followed by rice husk briquette, maize cob and wood chips respectively for IGS-2M. The smoke index test was done and compared with the standard smoke scale to find the extent of pollution and it is found at acceptable limits after the gas production has started. The socio-economic analysis shows that IGS-2F is feasible having a payback period of about 14 months and the cost benefit ratio of 4.0. Key Words: Institutional gasifier; Thermal efficiency; Smoke index and Socio-economic analysis etc. Journal of the Institute of Engineering, Vol. 7, No. 1, July 2009 pp. 142-149 doi: 10.3126/jie.v7i1.2074